2016
DOI: 10.13169/workorgalaboglob.10.1.0027
|View full text |Cite
|
Sign up to set email alerts
|

Reputation and trust on online labour markets: the reputation economy of Elance

Abstract: This article examines profile data about 9,593 freelancers from 121 countries active in the Design and Multimedia section of Elance, a major online labour market existing up until 2015. Using statistical analysis, the article evidences that the earnings a contractor obtains from working through Elance positively correlates with higher reputation scores and suggests that the conception of trust among actors operating on an online labour market resembles that which characterises e-commerce platforms like eBay or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Accordingly, algorithmic management has often been found to exercise ‘softer’ forms of control than traditional management, including ‘reputational control’ via the imposition of ‘information asymmetries’ in which client-generated discretionary feedback, reviews and ratings (stars, likes) are calculated, interpreted and rendered actionable by largely inscrutable and opaque processes of automation and computation. These factors all directly affect the standing and visibility of gig workers on the platform and hence their ability to earn a living (Rosenblat and Stark, 2016; Shapiro, 2018), since higher reputation scores correlate strongly with higher earnings on labour platforms (Gandini et al, 2016).…”
Section: Literaturementioning
confidence: 99%
“…Accordingly, algorithmic management has often been found to exercise ‘softer’ forms of control than traditional management, including ‘reputational control’ via the imposition of ‘information asymmetries’ in which client-generated discretionary feedback, reviews and ratings (stars, likes) are calculated, interpreted and rendered actionable by largely inscrutable and opaque processes of automation and computation. These factors all directly affect the standing and visibility of gig workers on the platform and hence their ability to earn a living (Rosenblat and Stark, 2016; Shapiro, 2018), since higher reputation scores correlate strongly with higher earnings on labour platforms (Gandini et al, 2016).…”
Section: Literaturementioning
confidence: 99%
“…The work of Pallais [44] illustrates this with experimental evidence: Freelancers with no prior work experience who received the experimental treatment-being hired for a project and obtaining positive feedback-almost tripled their relative income in comparison to the control group (not hired for a project). One of the coping strategies that freelancers use to accrue an initial reputation is selling labor at a substantially lower cost to attract the first clients [22]. Furthermore, empirical research has shown that poor reputation leads to lower bid amounts in auctions on the side of workers, to compensate for the perceived disadvantage due to a low reputation score [15].…”
Section: The (Unintended) Consequences Of Reputation Systemsmentioning
confidence: 99%
“…This means that there is a mix of employees in terms of the jobs that they have received in the past and the reputations that they have developed based on this. To model the distribution of the number of jobs that employees have received before, the number of previously received jobs comes from a random exponential distribution (with = 1∕2 ; rounded down to the nearest integer) where the majority of users received small number of jobs and a minority of users received a large number of jobs (see [22]). Earnings are initially set to zero, to track how much a given freelancer was able to earn since the start of the simulation.…”
Section: Modelling the Recruiting At Olmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have done some related research. Evidence have been found that the earnings a contractor obtains from working through crowdsourcing market positively correlates with higher reputation scores ( Gandini et al, 2016 ). In more detail, reputation has a significant impact on the transaction type of fixed-price contracts, but no obvious impact for time-material contracts ( Lin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%